Healthcare workers highly affected during the COVID-19 epidemic wave in Poland prior to vaccination availability: seroprevalence study - Magdalena Rosińska; Małgorzata Stępień; Wioleta Kitowska; Małgorzata Milczarek; Grzegorz Juszczyk; Zuzanna Nowacka; Aneta Gardel; Adam Hermann; Aneta Bardoń-Błaszkowska; Rafał Cudnik; Hanna Czubak; Magdalena Wolniak-Bińkowska; et al. (Nofer Institute of Occupational Medicine, 2022)
Background The aim of the study was to assess seroprevalence of anti-SARS-CoV-2 antibodies among healthcare workers (HCW) before introduction of vaccination, in selected areas in Poland as well as to identify potential risk factors and estimate the cumulative incidence of COVID-19 infections in this population. Material and Methods The authors conducted a sero-epidemiological, cross-sectional study among HCW of 5 non-COVID-19 hospitals in Poland. The recruitment took place in December 1-23, 2020, all HCW at selected hospitals could volunteer into the study. All persons were screened with rapid SARS-CoV-2 IgM/IgG tests in capillary blood. In case of positive result, 5 ml of venous blood was drawn for confirmatory testing with ELISA assay. The authors estimated prevalence of laboratory confirmed anti-SARS-CoV-2 antibody presence and examined factors associated with positive result. Cumulative incidence was estimated applying 2-source capture-recapture method to serology results and self-report of past infection. Results Out of 1040 HCW included in the analysis, one-fourth (25.2%) received a positive result for anti-SARS-CoV-2 antibodies by ELISA test, the prevalence among women was 25.3% (95% CI: 22.5-28.4) and 24.6% (95% CI: 19-31.2) among men. The prevalence of anti-SARS-CoV-2 antibodies was the highest among respondents who declared home contact with a confirmed COVID-19 case, 43.9% (95% CI: 32.4-56.1). It was also elevated among those who indicated contact with patients with COVID-19, 32.5% (95% CI: 26.7-38.8) and business contacts, including at the workplace, 28.9% (95% CI: 22.5-36.3). The estimated cumulative incidence of COVID-19 infections in the population, using the capture-recapture method was 41.2% (95% CI: 38.1-44.2). Conclusions Healthcare workers remained at increased risk of infection largely due to work-related contacts with infected patients, although home exposure was also common. Estimated cumulative incidence is higher than the antibody prevalence, which indicates the need to monitor HCW for possible immunity waning, also post-immunization immunity. Med Pr. 2022;73(2):109-23